The discrimination, perception, and production of two German /r/ allophones by two groups of American English speakers - Tepeli, Dilara (The Journal of the Acoustical Society of America, 2010)
The German /r/ sound is one of the most difficult sounds for American English (AE) speakers learning German as a foreign language. Part of this difficulty may be due to its rich phonetic variation. The standard German /r/ variant [R] and dialectal variant [R′] are achieved by varying the tongue constriction degree while keeping place of articulation constant [Schiller and Mooshammer (1995)]. The close articulatory proximity of these allophones provides an opportunity for testing the relationship between perception and production in L2 sound acquisition. The aim of this study is to investigate how well experienced AE speakers and naive AE speakers can discriminate and produce the difference between the uvular fricative [R] versus the uvular trill [R′]. Two groups of AE subjects who participated in an imitation study were prompted to produce single words beginning with either [R] or [R′]. Subjects also participated in a discrimination and categorization test. Preliminary results suggest that inexperienced AE can discriminate [R] versus [R′] well. They often perceive the sounds as /h/ and are more successful at producing [R′] than [R]. Experienced speakers also discriminate the two sounds well, perceive both sounds as the German /r/ and struggle more with producing [R′] than [R].